(untitled) (Hekima Review, 2016)
Child sacrifice which involves the killing or the removal of body parts of children is a harmful practice which is ravaging Uganda, a densely Christian nation. This paper aims to enable Christians in Uganda and beyond, to get involved in the fight against this practice, not only by condemning those involved in the practice but also by devising means of preventing this inhuman practice through community cohesion and adherence to ecclesial and civil norms. Several aspects will be highlighted. The paper will end by stressing the fact that fighting against child sacrifice is not only a responsibility of the civil and religious leaders but is for everybody and more so those who are Christians. We cannot profess to be true Christians if we turn a deaf ear to the vulnerable members of the society.